The thought of things in Francis Ponge and Georges Perec - Rodrigo Lelpo (Gragoatá, 2012)
This work intends to analyze the process of subjectification through the writing in the descriptive poetics of booth Francis Ponge and Georges Perec. Describing the banality of the world around them, Ponge and Perec establish a relation between things, man, and language through a narrative economy in which the more the subject describes his external space the more he approaches a search of himself.